One new record of the family Theraphosidae (Arachnida: Araneae) for Vietnam - Sac, Pham Dinh; Con, Vu Quang (Academia Journal of Biology, 2014)
The spider species Selenocosmia huwena (Theraphosidae) was identified by J. F. Wang (Hunan Normal University, China) in 1993 as a new species to science. This species was transferred to the genus Ornithoctonus by M. S. Zhu and D. X. Song in 2000. It distributed in the sourthern part of China and was an aggressive and venomous spider species. Recently, three specimens of Ornithoctonus huwena (Wang et al., 1993) were found in the Huulien nature reserve, Huulung district, Langson province and the Tamdao national park, Vinhphuc province. Detailed data about this new record to Vietnam were given.